Implementasi Algoritma C 4.5 Dalam Pembuatan Aplikasi Penunjang Keputusan Penerimaan Pegawai CV. X - Joko Purnomo, Wawan Laksito YS, Yustina Retno Wahyu U (STMIK Sinar Nusantara, 2012)
The problems are often found in the recruitment process is the difficulty of determining which candidate meet the criteria to be employees. Determining the prospective employees who meet the required criteria need appropriate recommendations. This research developed a system for selecting candidate that implements the C4.5 decision tree algorithm. The criteria used are the latest education, work experience who have ever lived, the age of the prospective employee, the value of a diploma transcript, the value written test, interview and test scores. In designing applications using context diagrams, and presentation applications using Code Gear RAD Studio Delphi 2009 and MySQL database. This research results is Decision Support System with C4.5 algorithm for selection and acceptance of the employees candidate.